New records of rare genera of the subfamily Rogadinae (Hymenoptera: Braconidae), with description of nine new species from Vietnam - Long, Khuat Dang; Hiep, Nguyen Duc; Hoa, Dang Thi; Nhi, Pham Thi (Academia Journal of Biology, 2018)
Six new species of three small genera of the subfamily Rogadinae: Cystomastacoides van Achterberg, 1997; Gyroneuron Kokujev, 1901 and Rogasodes Chen & He, 1997, viz. Cystomastacoides contrastus Long, sp. n.; Cystomastacoides similis Long, sp. n.; Gyroneuron asperatum Long, sp. n.; Gyroneuron bicoloratum Long, sp. n.; Gyroneuron glabrum Long, sp. n. and Rogasodes phongi Long & Hoa, sp. n.; and three new species of the subgenus Arcaleiodes Chen & He, 1997 from Vietnam, namely: Aleiodes (Arcaleiodes) hoanglienensis Long, sp. n., Aleiodes (Arcaleiodes) sapa Long, sp. n. and Aleiodes (Arcaleiodes) simulatus Long, sp. n. are described. Additionally, two genera: Cystomastacoides van Achterberg and Rogasodes Chen & He, and two species: Aleiodes (Arcaleiodes) sinamensis Quicke & Butcher and Cystomastacoides coxalis Chen & He are newly recorded for Vietnam’s braconid fauna. Illustrated keys to species of the genera Cystomastacoides, Gyroneuron and subgenus Arcaleiodes from Vietnam are given. The checklist and distribution of the already known species of the genera are also provided. Citation: Long KD, Hiep ND, Hoa DT, Nhi PT, 2018. New records of rare genera of the subfamily Doryctinae (Hymenoptera: Braconidae), with description of nine new species from Vietnam. Academia Journal of Biology, 40(3): xxx-xxx. https://doi.org/ *Corresponding author: khuatdanglong@gmail.com